A commitment-based reference ontology for services. (December 2015) - Nardi, Julio Cesar; Falbo, Ricardo de Almeida; Almeida, João Paulo A.; Guizzardi, Giancarlo; Pires, Luís Ferreira; van Sinderen, Marten J.; Guarino, Nicola; Fonseca, Claudenir Morais
Abstract: The concept of "service" has been characterized in different disciplines and by different authors from various points of view. This variety of characterizations has emerged because although this notion seems intuitive, it is far from trivial, with many interrelated perspectives. Given their importance in enterprise computing and Service Science in general, we believe that a clear account of services and service-related concepts is necessary and would serve as a basis for communication, consensus and alignment among approaches and perspectives. In this paper we propose a commitment-based account of the notion of service captured in a core reference ontology called UFO-S. We address the commitments established between service providers and customers, and show how such commitments affect the service lifecycle. Moreover, we show that the commitment-based account can serve to harmonize different notions of service in the literature. Highlights: We present a core reference ontology for services called UFO-S. UFO-S is based on the notion of service commitments and claims. UFO-S focuses on service offer, service negotiation, and service delivery phases. UFO-S is grounded in the Unified Foundational Ontology (UFO). This ontology is applied for harmonizing a number of service perspectives.